1995
DOI: 10.1111/j.1750-3639.1995.tb00580.x
|View full text |Cite
|
Sign up to set email alerts
|

The Neuropathology and Epidemiology of Bovine Spongiform Encephalopathy

Abstract: Bovine spongiform encephalopathy (BSE), defined originally from its characteristic neuropathology, retains a place of particular interest in the scrapie-like or prion disease group, presenting uniquely an example of such diseases occurring as a nationwide food-borne epidemic in Great Britain. Comprehensive monitoring of the epidemic, both pathologically and epidemiologically, has facilitated our present understanding of the disease. BSE presents the classical neuropathological features of the transmissible spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
131
1
5

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(160 citation statements)
references
References 48 publications
23
131
1
5
Order By: Relevance
“…In BSE, we observed the typical caudorostral decrease in severity of the lesions described in natural and experimental BSE (21,22), confirmed by the general shape of the lesion profile (Fig. 2).…”
Section: Resultssupporting
confidence: 49%
“…In BSE, we observed the typical caudorostral decrease in severity of the lesions described in natural and experimental BSE (21,22), confirmed by the general shape of the lesion profile (Fig. 2).…”
Section: Resultssupporting
confidence: 49%
“…Although observed in only two cattle, the BASE phenotype could be more common than expected. In previous studies, amyloid congophilic plaques were found in 1 of 20 BSE cases examined systematically for amyloid (23), and it was reported that focal cerebral amyloidosis is present in a small proportion of BSE cases (24). Although no biochemical analysis of PrP Sc glycotype is available for these animals with ''atypical BSE phenotype,'' our present results underscore the importance of performing a strain-typing in bovine TSE with amyloid deposition.…”
Section: Bovine Amyloidotic Spongiform Encephalopathy (Base): a Secondmentioning
confidence: 52%
“…However, such plaques are not a feature of all species (Prusiner 1996). Indeed, such plaques are rarely observed in the brains of BSE-infected bovines (Wells and Wilesmith 1995). The probability of ingesting a dose of BSE prions approaching the human oral ID 50 in a single exposure through the aquatic environment is remote because of molecular dispersion and dilution of the prions.…”
Section: Bse Agent Will Be Dispersed and Diluted To A Large Degree Inmentioning
confidence: 99%
“…In particular, PrP Sc can form long rods under certain extraction conditions . Large plaques containing aggregated PrP-res are rare in brains of BSE-infected bovines (Wells and Wilesmith 1995), although they are a feature of some prion diseases including vCJD in humans Almond and Pattison 1997).…”
Section: The Biological Nature Of the Bse Agentmentioning
confidence: 99%